2013
DOI: 10.1155/2013/739029
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Peginterferonα-2a and Peginterferonα-2b, Both plus Ribavirin, for Chronic Hepatitis C: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background. The efficacy and tolerability of peginterferon α-2a and peginterferon α-2b in chronic hepatitis C (CHC) patients remain controversial. Methods. PubMed, Ovid, and Cochrane libraries were electronically searched until August 30, 2012. Studies that met the inclusion criteria were systematically evaluated by two reviewers independently. Results. The overall sustained virologic response (SVR) rate of the peginterferon α-2a group was significantly higher than that of the peginterferon α-2b group (46.7% v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Several previous meta-analyses have reported that PEG-IFN-alfa-2a was associated with higher SVR rates than PEG-IFN-alfa-2b [28][31]. Treatments with PEG-IFN-alfa-2a might obtain a similar or decreased discontinuation rate than PEG-IFN-alfa-2b [28], [31]. The results of this study confirmed the improved treatment outcome of PEG-IFN-alfa-2a (adjusted OR, 2.91; 95% CI, 1.75–4.83).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several previous meta-analyses have reported that PEG-IFN-alfa-2a was associated with higher SVR rates than PEG-IFN-alfa-2b [28][31]. Treatments with PEG-IFN-alfa-2a might obtain a similar or decreased discontinuation rate than PEG-IFN-alfa-2b [28], [31]. The results of this study confirmed the improved treatment outcome of PEG-IFN-alfa-2a (adjusted OR, 2.91; 95% CI, 1.75–4.83).…”
Section: Discussionmentioning
confidence: 96%
“…The higher bioavailability of PEG-IFN-alfa-2a may be linked to the treatment efficacy [27]. Several previous meta-analyses have reported that PEG-IFN-alfa-2a was associated with higher SVR rates than PEG-IFN-alfa-2b [28][31]. Treatments with PEG-IFN-alfa-2a might obtain a similar or decreased discontinuation rate than PEG-IFN-alfa-2b [28], [31].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, based on the monoinfection analysis, physicians may prefer to utilize pegylated α-interferon 2a [89]. Ribavirin should always be given based on weight (1000 mg per day if less than 75 kg and 1200 mg per day if above this weight) [90].…”
Section: Rationalementioning
confidence: 99%
“…Numerous researchers have found that PegIFNα-2a plus ribavirin yields a higher SVR and a lower discontinuation rate than PegIFN-α-2b plus ribavirin [8][9][10]. However, a review article found that PegIFN-α-2a and PegIFNα-2b exhibit similar degrees of effectiveness and tolerability, with few clinical differences [11].…”
Section: Introductionmentioning
confidence: 99%